Electromechanically Active As‐Electrospun Polystyrene Fiber Mat: Significantly High Quasistatic/Dynamic Electromechanical Response and Theoretical Modeling. Issue 14 (29th June 2020) - Ishii, Yuya; Yousry, Yasmin Mohamed; Nobeshima, Taiki; Iumsrivun, Chonthicha; Sakai, Heisuke; Uemura, Sei; Ramakrishna, Seeram; Yao, Kui
Abstract: Flexible and lightweight pressure sensors have attracted tremendous attention as a promising component of wearable biological motion sensors and artificial electronic skins. Here, the electromechanical response of as‐electrospun fiber mats composed of a commodity polymer, atactic polystyrene, which can be applied in low‐cost/large‐area, flexible, and lightweight pressure sensors is demonstrated. The fiber mat demonstrates a significantly high apparent converse piezoelectric constant of >30 000 pm V −1 under static measurement and ≈13 000 pm V −1 even at a high frequency of 1 kHz. The first theoretical model to explain the unique electromechanical response is constructed, which reveals that the softness and moderate charge of the fiber mat are the reasons for the significantly high electromechanical response. Further, apparent piezoelectric constants obtained by direct measurement are lower than those obtained by the converse measurement, which is attributed to the densification and hardening of the fiber mat due to prepressure applied in direct measurement. These findings are likely to serve as a milestone for the development of large‐area, flexible, and lightweight pressure sensors at low cost, as well as highly movable actuators like optical modulators without a substantial mechanical load. Abstract : A large electromechanical response of as‐electrospun fiber mats composed of a commodity polymer, atactic polystyrene, is demonstrated. The fiber mat apparently shows a high effective converse piezoelectric constant of >30 000 pm V −1 under static measurement conditions and ≈13 000 pm V −1 at 1 kHz. A theoretical model is constructed to explain the significant effective electromechanical response.